Prevalence of the excessive daytime sleepiness in Russian Federation - A. L. Kalinkin (Нервно-мышечные болезни)
Background. Excessive daytime sleepiness is a very important symptom of a wide range of pathological conditions and has a significant impact on both the individual patient and the society as a whole. Estimation of the prevalence of excessive daytime sleepiness, identifying the cause, and also its elimination is an important socio-economic task.Objective to estimate the prevalence of excessive daytime sleepiness in the population of the Russian Federation according to the Internet survey data and the distribution of the estimate of the daytime sleepiness by age and body mass index.Materials and methods. One-time study according to the Internet survey data on the Epworth drowsiness scale (ESS).Results. Excessive daytime sleepiness (more than 10 points on the ESS scale) was observed in 40,9% of respondents.Conclusion. According to the results of the study, excessive daytime sleepiness is widespread in the Russian Federation, which speaks of its socio-economic significance, the need for measures to identify its causes and their elimination.